2008
DOI: 10.1159/000190788
|View full text |Cite
|
Sign up to set email alerts
|

A Mutation in the Mouse Chd2 Chromatin Remodeling Enzyme Results in a Complex Renal Phenotype

Abstract: Background and Aims: Glomerular diseases are the third leading cause of kidney failure worldwide, behind only diabetes and hypertension. The molecular mechanisms underlying the cause of glomerular diseases are still largely unknown. The identification and characterization of new molecules associated with glomerular function should provide new insights into understanding the diverse group of glomerular diseases. The Chd2 protein belongs to a family of enzymes involved in ATP-dependent chromatin remodeling, sugg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 68 publications
0
23
0
Order By: Relevance
“…RNA silencing targeted at p22phox is also reported to attenuate the increase in NADPH oxidase activity, oxidative stress, and a progressive rise in blood pressure of conscious rats during the second week of an Ang II infusion [39]. Reduction in renal cortical expression of p22phox is accompanied by reduced expression of various NADPH oxidases (Nox-1, Nox-2, and Nox-4) with increased expression of p47phox, also known as cytosol factor 1, which is activated to produce superoxide anion during the respiratory burst associated with oxidative stress [40].…”
Section: The 47-kda Subunit Of Nadph Oxidase Oxidative Stress and Amentioning
confidence: 99%
See 1 more Smart Citation
“…RNA silencing targeted at p22phox is also reported to attenuate the increase in NADPH oxidase activity, oxidative stress, and a progressive rise in blood pressure of conscious rats during the second week of an Ang II infusion [39]. Reduction in renal cortical expression of p22phox is accompanied by reduced expression of various NADPH oxidases (Nox-1, Nox-2, and Nox-4) with increased expression of p47phox, also known as cytosol factor 1, which is activated to produce superoxide anion during the respiratory burst associated with oxidative stress [40].…”
Section: The 47-kda Subunit Of Nadph Oxidase Oxidative Stress and Amentioning
confidence: 99%
“…CHD2 may, therefore, function as an epigenetic regulator of gene expression by modifying chromatin structure and altering access of transcription factors, such as RNA polymerases, to the transcription sites on the chromosome where the DNA template for RAS genes resides. Chd2-mutant mice exhibit proteinuria resulting from glomerular disease [40].…”
Section: The 47-kda Subunit Of Nadph Oxidase Oxidative Stress and Amentioning
confidence: 99%
“…As shown in supplementary Table 3, the rs9469220 obtained supporting evidence (''1f'' score) from eQTL and TF binding/Dnase peak, and rs3135377 obtained supporting evidence (''6'' score) from others. Specifically, HLA-DQB1, the corresponding gene for rs9469220, was shown to be bonded to several proteins such as CHD2, an important regulator of both the function of kidney and islet that may be associated with DN (Dreja et al 2010;Marfella et al 2008). Results from UCSC showed that both genes have low conservation scores that demonstrate low evolutionary constraint and may result in high-probability allele mutation among different specie in evolution development.…”
Section: Resultsmentioning
confidence: 99%
“…A small proportion (2/15) of heterozygous mice have eye defects [87]. A distinct Chd2 mutant mouse model with a mutation that abrogates the DNA-binding activity of Chd2 has delayed embryogenesis and perinatal lethality [125,126]. Surviving heterozygous mice have an enhanced susceptibility to damage in many primary organs, in particular the kidney and heart [125,126].…”
Section: Chd Proteins In Developmental Disordersmentioning
confidence: 99%
“…A distinct Chd2 mutant mouse model with a mutation that abrogates the DNA-binding activity of Chd2 has delayed embryogenesis and perinatal lethality [125,126]. Surviving heterozygous mice have an enhanced susceptibility to damage in many primary organs, in particular the kidney and heart [125,126]. The diverse developmental defects exhibited by Chd2-deficient mice indicate that Chd2 plays important roles in the development of multiple tissues and organs.…”
Section: Chd Proteins In Developmental Disordersmentioning
confidence: 99%